Strategic collaborations between Universiti Teknologi MARA (UiTM) and Akademi Farmasi Yogyakarta (AFIYO) in advancing natural products for the pharmaceutical industry – preliminary findings from pre- and post-webinar assessments - Ibrahim, Nurul Alyaa; Muhsain, Siti Nur Fadzilah; Mokhtar, Nur ‘Ainun (Universiti Teknologi MARA, Kedah, 2024)
In the modern pharmaceutical industry, incorporating natural products into drug development is getting significant attention due to their potential therapeutic benefits. Pharmapreneur- is the term used to merge the concept of pharmaceuticals with entrepreneurial ventures. In Malaysia, exposure to and development of pharmapreneurship is limited compared to Indonesia. Therefore, a collaborative webinar is needed to share knowledge with the community and students from both countries. The main objective of this study is to measure the level of understanding before and after the webinar. This study employed convenience sampling to evaluate participants' knowledge before and after the webinar using simple questions. Additionally, participants assessed the speaker's efficiency in delivering and addressing questions on the topics covered. Results were analyzed using Statistical Package for Social Sciences (SPSS) version 28.0 and presented in tables and percentages. A total of 388 participants joined the webinar session and more than 50% of them were females. There were significant differences in the level of understanding before (M=3.54) and after (M=4.23) the webinar; z (-10.98), p=<0.001. In conclusion, these preliminary findings serve as a benchmark for authorized institutions in providing knowledge and training in preparing Malaysia; particularly UiTM towards Pharmapreneur; a field deemed to have a bright future ahead.